2018
DOI: 10.1161/atvbaha.117.309897
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of IL (Interleukin)-1β in Neutrophil Extracellular Trap Formation and Abdominal Aortic Aneurysms

Abstract: Altogether, the results suggest a dominant role of IL-1β-induced NETosis in AAA formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
172
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(182 citation statements)
references
References 29 publications
8
172
0
2
Order By: Relevance
“…The triggers of NETosis in COVID-19 are potentially myriad and will require further investigation. Possibilities include virus-damaged epithelial cells (13,29), activated platelets (30,31), activated endothelial cells (32), and inflammatory cytokines such as IL-1β (19,33), IL-8 (34,35), granulocyte colony stimulating factor (36,37), and likely others (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The triggers of NETosis in COVID-19 are potentially myriad and will require further investigation. Possibilities include virus-damaged epithelial cells (13,29), activated platelets (30,31), activated endothelial cells (32), and inflammatory cytokines such as IL-1β (19,33), IL-8 (34,35), granulocyte colony stimulating factor (36,37), and likely others (17).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has yet to be assessed whether NETs contribute to the inflammatory storm that leads to respiratory failure in many COVID-19 patients, there is emerging evidence to implicate inflammatory cytokines such as interleukin (IL)-1β and IL-6 in the COVID-19 milieu (17). Not surprisingly, NETs are intimately intertwined with both cytokines, and especially IL-1β, in many pulmonary and cardiovascular diseases (8,(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cytokine storms lead to acute lung injury, ARDS, and death (Channappanavar and Perlman, 2017; Chousterman et al, 2017). It is especially noteworthy that NETs can induce macrophages to secrete IL1β and that IL1β enhances NET formation in various diseases, including aortic aneurysms and atherosclerosis (Kahlenberg et al, 2013; Meher et al, 2018; Sil et al, 2017; Warnatsch et al, 2015). Together, these data suggest that under conditions in which the normal signals to dampen inflammation are lost, such as during a cytokine storm, a signaling loop between macrophages and neutrophils can lead to uncontrollable, progressive inflammation.…”
Section: Nets and The Cytokine Stormmentioning
confidence: 99%
“…In addition, we observed that NETs were predominantly located in the subepithelial layer of nasal polyp tissue (Figure A). Typical NETs were extracellular cloud structures that stained positive for DNA and MPO (Figure B), which was further confirmed by additional IF staining positive for DNA, MPO, and citrullinated histone H3 (Cit‐H3), a marker for NET formation (Figure ). As expected, the number of NETs was highly correlated with that of neutrophil in nasal tissues (Figure F), and NET count and NETs% were significantly increased in Neu‐NP compared with Non‐Neu‐NP (Figure G‐H).…”
Section: Resultsmentioning
confidence: 65%